Moroccan Arabic aspect in conversation: Evolution of the imperfective through use - Georgia Zellou (Journal of Modern Languages)
Dialectal Moroccan Arabic has two distinct morphological forms of the imperfective where Standard Arabic had one. Previous studies have claimed that the difference in function in the two imperfectives is one of mood. However, using naturally occurring conversation data this paper looks more closely at the use of the two imperfectives in Moroccan Arabic and comes to a different conclusion. Specifically, the older unmarked imperfective has been generalised as the â€œelsewhereâ€ condition, following Dryer (1995), while the newer marked imperfective is being used in contexts to express progressive and habitual aspect. This paper examines the evolution of the imperfective aspect in one dialect of Arabic through the framework of Conversation Analysis (CA).